ETHICAL AND PEDAGOGICAL IMPLICATIONS OF DEEP LEARNING INTEGRATION IN FOURTH GRADE CLASSROOMS: A CASE STUDY AT SDN 100801 PASAR SEMPURNA - Masrianti Ritonga; Rita Nur’ain Harahap; Yusti Andayati Pasaribu; Anita Adinda (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines the ethical and pedagogical implications of deep learning integration in fourth-grade classrooms at SDN 100801 Pasar Sempurna, Indonesia. Through classroom observations, semi-structured interviews with teachers, and document analysis, the research found that deep learning applications significantly improved student engagement and individualized learning outcomes. However, ethical concerns emerged regarding data privacy, unequal access to digital tools, and limited teacher preparedness. Teachers expressed uncertainty in balancing technological autonomy with moral and pedagogical control. The study concludes that while deep learning supports more adaptive and inclusive learning environments, its ethical implementation remains constrained by insufficient institutional policies and digital literacy. Strengthening teacher competence and establishing transparent ethical frameworks are crucial for ensuring responsible AI integration in primary education. These findings provide practical insights into balancing innovation and ethics in early educational contexts.